2012
DOI: 10.1371/journal.pone.0052870
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Interaction between Circumsporozoite Protein-Specific T Cell and Antibody Responses and Risk of Clinical Malaria Episodes following Vaccination with RTS,S/AS01E

Abstract: The candidate malaria vaccine RTS,S/AS01E provides significant but partial protection from clinical malaria. On in vitro circumsporozoite protein (CSP) peptide stimulation and intra-cellular cytokine staining of whole blood taken from 407 5–17 month-old children in a phase IIb trial of RTS,S/AS01E, we identified significantly increased frequencies of two CSP-specific CD4+ T cells phenotypes among RTS,S/AS01E vaccinees (IFNγ-IL2+TNF− and IFNγ-IL2+TNF+ CD4+ T cells), and increased frequency of IFNγ-IL2-TNF+ CD4+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
3
38
0
2
Order By: Relevance
“…6,8,9,[21][22][23] No systematic vaccine-induced CD8 + T cell response was detected in PBMCs in our study, which was consistent with other studies that showed RTS,S/AS induces little or no detectable CD8 + T cell response. 6,11,21,24,25 The anti-CS humoral immune responses in this study tended to be lower than those observed following administration of 3 doses of RTS,S/AS01 or RTS,S/AS02 to malaria-experienced children in Africa 13,14 but higher than those in African adults in a high malaria transmission area. 12 Overall, in all studies including the present trial, RTS,S/AS formulations produced robust anti-CS antibody responses, with the AS01 adjuvanted vaccine inducing higher responses than the AS02 adjuvanted formulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6,8,9,[21][22][23] No systematic vaccine-induced CD8 + T cell response was detected in PBMCs in our study, which was consistent with other studies that showed RTS,S/AS induces little or no detectable CD8 + T cell response. 6,11,21,24,25 The anti-CS humoral immune responses in this study tended to be lower than those observed following administration of 3 doses of RTS,S/AS01 or RTS,S/AS02 to malaria-experienced children in Africa 13,14 but higher than those in African adults in a high malaria transmission area. 12 Overall, in all studies including the present trial, RTS,S/AS formulations produced robust anti-CS antibody responses, with the AS01 adjuvanted vaccine inducing higher responses than the AS02 adjuvanted formulation.…”
Section: Discussionsupporting
confidence: 91%
“…3,4 Anti-CS antibody titers and, to a lesser extent, CS-specific CD4 + T cells elicited by RTS,S have been identified as immunological markers associated with protection. [5][6][7] CS-specific CD4 + T cells induced by RTS,S produce a mixture of cytokines, such as interleukin (IL)-2, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ. [7][8][9][10][11] In phase 2 clinical trials of adults and children, the RTS,S/AS01 formulation had an improved immunogenicity profile, in terms of humoral and cell-mediated immune (CMI) responses, and an equally favorable safety profile as compared with RTS,S/AS02.…”
Section: Introductionmentioning
confidence: 99%
“…However, as described earlier, CSP-specific immunity is not absolutely necessary or sufficient to attain immunological protection against challenge (11,(21)(22)(23)(24). Thus, there is a need to identify individual immunogenic antigens so that they can be evaluated for inclusion in multicomponent subunit vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CSP-based RTS, S vaccine in phase 3 human trials does not trigger strong CTL responses (18,19). The partial protection (20) from RTS,S is instead associated with antibodies and CD4 + T-cell responses (21). Thus, CSP is an important but currently insufficient target for use as a single-antigen vaccine.…”
mentioning
confidence: 99%
“…During the preclinical and clinical evaluations of these candidate vaccines, both Ag-specific Ab and CD4 + T cell responses have been consistently observed, suggesting that AS01 promotes these adaptive responses irrespective of the type of Ag used (2). In the case of the malaria vaccine candidate, these adaptive responses have been associated with protection against malaria in various clinical trials (23)(24)(25)(26) and have supported the selection of AS01 over other adjuvants (2,23,27).…”
mentioning
confidence: 94%